2015
DOI: 10.1128/aem.02222-15
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling Potential of a Grassland Litter Microbial Community

Abstract: bBecause microorganisms have different abilities to utilize nitrogen (N) through various assimilatory and dissimilatory pathways, microbial composition and diversity likely influence N cycling in an ecosystem. Terrestrial plant litter decomposition is often limited by N availability; however, little is known about the microorganisms involved in litter N cycling. In this study, we used metagenomics to characterize the potential N utilization of microbial communities in grassland plant litter. The frequencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 89 publications
7
31
1
Order By: Relevance
“…The balance between DNRA and denitrification, which leads to the loss of N to the atmosphere, is thought to be key to soil N budgets. Our results confirm previous studies suggesting that this pathway may be more common than previously thought (45,46), but the taxa encoding the process in soil environments remain to be carefully characterized (47).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The balance between DNRA and denitrification, which leads to the loss of N to the atmosphere, is thought to be key to soil N budgets. Our results confirm previous studies suggesting that this pathway may be more common than previously thought (45,46), but the taxa encoding the process in soil environments remain to be carefully characterized (47).…”
Section: Discussionsupporting
confidence: 82%
“…In each metagenomic library, we searched for sequences from eight N pathways, defined previously in ref. 46. These pathways included nitrification (number of genes targeted: n = 2), N fixation (n = 20), denitrification (n = 20), dissimilatory nitrate to nitrite reduction (n = 9), dissimilatory nitrite to ammonia reduction (n = 4), assimilatory nitrate to nitrite reduction (n = 2), assimilatory nitrite to ammonia reduction (n = 2), and ammonia assimilation (n = 10) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, all classes of Proteobacteria were more abundant in the biochar-amended samples, consistent with our previous study (22) in which we observed that biochar increased Proteobacteria abundance in the oxisol as early as 1 month and up to 1 year after the initial amendment. Notably, the orders Rhizobiales and Burkholderiales were most abundant and higher in biochar-amended samples and have been characterized as N fixers and more broadly as N-cycling generalists, carrying genes for the majority of the assimilatory and dissimilatory N pathways (45). Furthermore, some members of both bacterial orders have the ability to degrade recalcitrant compounds, including some naturally occurring aromatic compounds and organic contaminants such as those used as pesticides, herbicides, or fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, while large databases of protein-based HMMs exist, several specialized HMM databases have been recently introduced for metagenomic annotation. For example, FOAM 119 is a database designed to identify genes matching KEGG Orthology groups 116,120 that can aid in characterizing the metabolic potential of communities 121,122 . Resfams 108 , on the other hand, was developed to recognize the structure of antibiotic resistance genes and has been used to study the human gut resistomes of different cultures 123,124 .…”
Section: High-resolution Characterization Of the Microbiome's Functiomentioning
confidence: 99%